KEPERCAYAAN MASYARAKAT JAWA TERHADAP SANTET, WANGSIT, DAN ROH MENURUT PERSPEKTIF EDWARDS EVANS-PRITCHARD - Ening Herniti (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
Javanese society is known as a religious community. Most of them as Muslim, but in everyday life they still believe in mystical things. One of thecommunity in Java believe that witchcraft is exist and real in this world.Witchcraft is negative energy that can damage a person's life in the form of thedisease, destruction of household until death. In addition, they also believewith wangsit. The term of wangsit often called as the inspiration, guidance,word, guidance, dhawuh (command), or wisik (whisper) invisible from God.Only the chosen people will be able to receive wangsit, that is, those whodiligently draw closer to God, look for the essence of life, and doing laku. Lakuis doing various forms of fasting as not eating or drinking for a certain period,mutih (only eat white rice), ngrowot (only eat fruits), and others. Furthermore, Javanese people also believe in the existence of spirit strength, such as belief toanimism, dynamism, and totemism.